Contribuição metodológica à engenharia diagnóstica para aplicação à conservação da infraestrutura rodoviária: estudo de caso da sinalização da SP 310 – Rodovia Washington Luís - Reis, Lucas Vinícius Nogueira dos (Universidade Federal de São Carlos, 2020)
In general, the present work aims to verify the applicability of the concepts of Diagnostic Engineering for the conservation of highway infrastructure. Therefore, in this research, adaptations and improvements were made to the inspection tool, in order to enable decision makers, coming from private companies and public entities, access of a logical process of prioritizing highway maintenance. The element studied was the highway signaling of the SP 310- Washington Luis Highway. Two methods were used to estimate the prioritization weights of maintenance in highway signaling: the method of analysis of potencial failure, represented by the FMEA (Failure Mode and Effects Analysis) and the multicriteria analysis method, represented by the AHP (Analytic Hierarchy Process). For the application of the FMEA method, the computer program TopEventFTA® was firstly used, resulting in the survey of all possible anomalies in highway signaling. Then, unstructured interviews were carried out with two transport regulation specialists from the Sao Paulo State Transport Regulatory Agency (ARTESP), in order to obtain the severity and the probability detection indexes for each anomaly, since the occurrence index was obtained by the ARTESP database, for the month of January 2019. The multiplication of these indexes provided the weight of maintenance priority in highway signaling by the FMEA method, on a scale from 0 to 1,000 (one thousand). For the application of the AHP method, a questionnaire was firstly presented on GoogleForms®, to 21 (twenty-one) professionals linked to highway signaling, making it possible to carry out the pairwise comparisons regarding the priority of maintenance between anomalies in vertical highway signaling. The predominant values of these pairwise comparisons were placed in the TransparentChoice® program, resulting in a maintenance priority weight for each anomaly in vertical highway signaling, on a scale from 0 to 100%. The result of the FMEA method for the inspection of highway signaling showed that the maintenance priority obtained by the referred method is different for each concessionaire, since it depends on the anomaly occurrence index in each stretch. While for concessionaire 1 the maintenance priority was the absence of the regulation plate (weight of 360), for concessionaire 2 the maintenance priority was the absence of soil paint (weight of 441). The application of the AHP method to the vertical highway signaling showed that the order of maintenance priority obtained by this method is given by the following weights: absence of plate (48%), covered plate (39%), damaged plate (9%) and plate non-standard (4%).
Methodological contribution to diagnostic engineering for application to the conservation of highway infrastructure: case study of the signaling of SP 310 - Washington Luís
Keywords: Engenharia diagnóstica em rodovias; Conservação de sinalização rodoviária; Método FMEA em sinalização rodoviária; Método AHP em sinalização rodoviária; Diagnostic engineering on highways; Conservation of highway signaling; FMEA method in highway signaling; AHP method in highway signaling; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL